Functional characterization of three adenosine receptor types - Gurden, M.F. (1993)
1 The purpose of the present study was to classify adenosine receptors into A(1) and A(2) subtypes in a wide range of isolated tissues and cell types (rat adipocytes and atria, guinea-pig ileum and atria (A(1)); guinea-pig aorta, dog coronary artery and human platelets and neutrophils (A(2))) using the R- and S-diastereoisomers of N-phenylisopropyladenosine (PIA), N-cyclopentyladenosine (CPA), the novel compound, N-[(1S,trans)-2-hydroxycyclopentyl]adenosine (GR79236), N-[(2-methylphenyl)methyl]adenosine (metrifudil), 2-(phenylamino)adenosine (CV1808), and 2-[[2-[4-(2-carboxyethyl)phenyl]ethyl]amino]-N-ethylcarboxamidoadenosine (CGS21680); N-ethylcarboxamidoadenosine (NECA) was used as a standard. 2 Results obtained in all tissue preparations previously reported to contain A(1)-receptors could be described by a single rank order of agonist potency: CPA ≥ GR79236, R-PIA ≥ NECA >> S-PIA ≥ metrifudil ≥ CV1808, CGS21680. 3 In contrast, two distinct rank orders of agonist potency were observed in preparations previously reported to contain A(2)-receptors. In dog coronary artery, human neutrophils and platelets the rank order of potency was: CV1808, CGS21680 ≥ NECA > R-PIA ≥ metrifudil ≥ CPA > GR79236, S-PIA. However, in guinea-pig aorta the rank order was: NECA > metrifudil > R-PIA, CPA > CV1808, GR79236 ≥ S-PIA, CGS21680. 4 The results of this study are consistent with the existence of three types of adenosine receptor: A(1)-and two subtypes of A(2)-receptor. The receptor present in dog coronary artery, human platelets and neutrophils, probably corresponds to the A(2a) subtype, whilst that present in the guinea-pig aorta may be of the A(2b) subtype.